A assistência oficial para o desenvolvimento na política externa japonesa - Aragusuku, Juliano Akira de Souza (2011)
Japan is one of the main actors at the International System, with expressive capacity in the economic dimension and low expression in the strategic and political dimensions. Thus, Japan emphasized its performance in the international scene through the economic way, being distinguished, until the present moment, as one of the main actors in the international cooperation for development disbursing Official Assistance for Development (ODA). However, it would be ingenuous to assume that the supply of assistance to the developing countries occurs in reason of altruistic positions. Therefore, the objective is to analyze how the ODA is inserted in the context of the Japanese foreign policy. Initially we will evaluate the theoretical explanations developed in the field of the International Relations on the developed countries‟ aid disburses, emphasizing the case of Japan. Thus, we will seek to identify the motivations that support the Japanese ODA, using an empirical research. It is intended, finally, the comprehension about the Japanese uses of ODA to promote its interests, marking its position in the game of the international relations